PRODUCTION OF HYDROCARBONS FROM ORGANIC NANOPORES: A COMPREHENSIVE STUDY USING MOLECULAR SIMULATIONS - Perez Valencia, Felipe (My University, 2020)
Molecular models of organic pores are created using molecular dynamics simulations to investigate fluid behavior of confined reservoir fluids and fluid transport through nanoporous shales, aiming to reveal the underlying physics laws that govern the phenomenology that occurs at molecular scale. This is done through a study of the spatial distribution of fluids within organic pores, followed by the exploration of the fluid transport mechanisms during primary depletion from a molecular point of view. Finally, huff-n-puff enhanced oil recovery simulations are designed to examine the mechanisms that govern hydrocarbon recovery in shale rocks. The general observations are experimentally confirmed, providing a unique understanding of shales and the means by which oil and natural gas are produced.
Keywords: Hydrocarbon production; Unconventional reservoirs; Enhanced oil recovery; Molecular simulations